Size of gastroesophageal varices: its behavior after the surgical treatment of portal hypertension - Strauss, Edna; Sakai, Paulo; Gayotto, Luiz Carlos da Costa; Cardoso, Rita Antonelli; Forster, Sonia; Raia, Silvano (Revista do Hospital das Clínicas, 1999)
The size of gastroesophageal varices is one of the most important factors leading to hemorrhage related to portal hypertension. An endoscopic evaluation of the size of gastroesophageal varices before and after different operations for portal hypertension was performed in 73 patients with schistosomiasis, as part of a randomized trial: proximal splenorenal shunt (PSS n=24), distal splenorenal shunt (DSS n=24), and esophagogastric devascularization with splenectomy (EGDS n=25). The endoscopic evaluation was performed before and up to 10 years after the operations. Variceal size was graded according to Palmer's classification: grade 1 -- up to 3 mm, grade 2 -- from 3 to 6 mm, grade 3 -- greater than 6 mm, and were analyzed in four anatomical locations: inferior, middle or superior third of the esophagus, and proximal stomach. The total number of points in the pre-operative grading minus the number of points in the post-operative grading gave a differential grading, allowing statistical comparison among the surgical groups. Good results, in terms of disappearance or decrease of variceal size, were observed more frequently after PSS than after DSS or EGDS - 95.8%, 83.3%, and 72%, respectively. When differential grading was analyzed, a statistically significant difference was observed between PSS and EGDS, but not between proximal and distal splenorenal shunts. In conclusion, shunt surgeries were more efficient than devascularization in diminishing variceal size.